A Study on Bipolar Transurethral Resection of Prostate (TURP) versus Transurethral Resection and Electrovaporization (TURP-TUVP) Sandwich Procedure (Bangladesh Journal of Urology, 2022)
Background: TURP is the gold standard for the endoscopic treatment of BPH. Nonetheless, it remains associated with significant morbidity, especially in terms of hemorrhage leading to possible blood transfusion and delayed hospital discharge. TUVP is associated with reported improvements in subjective and objective measures but a high rate of postoperative irritative symptoms and lack of tissue for histologic examination. The concept behind TURP and TUVP sandwich procedure is to overcome the drawbacks of the two procedures.Objective: To compare the outcome of bipolar transurethral resection of prostate (TURP) and bipolar transurethral resection and electrovaporization of prostate (TURP-TUVP) sandwich procedure in patient with benign prostatic hyperplasia.Methods: This quasi experimental study was conducted in the Department of Urology, National Institute of Kidney Diseases and Urology (NIKDU), Dhaka, Bangladesh from July 2017 to June 2019 over a period of 2 years. Sixty patients with BOO caused by benign prostatic hyperplasia scheduled for transurethral resection of prostate were included in this study. Patients were selected first by purposive sampling and were grouped into A and B with randomization. Group A patients underwent bipolar TURP while group B patients underwent sandwich method. Perioperative findings as well as IPSS Qmax and PVR after 3 months of operation were compared.Results: Operative time was significantly longer in TURP-TUVP group than in TURP group (P value 0.036).Post operative hospital stay was significantly longer in TURP group (P value